Pharmacological Treatments for Hypochondriasis: A Review - Louw, Kerry-Ann; Hoare, Jacqueline; J. Stein, Dan (Current Psychiatry Reviews, 2014)
Despite the high prevalence of hypochondriasis in primary care settings, there are relatively few pharmacotherapy trials in hypochondriasis. Ongoing controversy about nosology of hypochondriasis and lack of work demonstrating specific neurobiological alterations in hypochondriasis may contribute to this. There have been several open label trials of selective serotonin reuptake inhibitors (SSRIs) and serotonin-2A antagonist/reuptake inhibitors (SARIs) for the treatment of hypochondriasis, and more recently two randomized controlled trials (RCTs). Taken together, there is a small body of evidence to support the efficacy of SSRIs in the treatment of hypochondriasis. Further RCTs are needed to confirm efficacy, determine effectiveness of treatments in primary care settings, address influence of comorbidity and other potential predictors of outcome, and compare pharmacotherapy to psychotherapy.
Keywords: neurobiology